2019
DOI: 10.1007/s40093-019-0274-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing growth and yield of crops with nutrient-enriched organic fertilizer at wet and dry seasons in ensuring climate-smart agriculture

Abstract: Purpose Rapid nutrient depletion in soils is one of the major problems that affect food production and food security in Sub-Saharan Africa. Studies have linked the growth of food crops with seasonal variation and differences in weather conditions. This study was conducted to assess the effects of various organic fertilizer formulations (OFFs) on the growth and yield of selected crops (Zea mays L.; Glycine max, TX 114 and Dioscorea rotundata Poir) during rainy and dry seasons to ensuring climate-smart agricultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 22 publications
4
17
0
2
Order By: Relevance
“…The results of this experiment showed that fertilizer treatment combinations had significant differences in all the morphological parameters of burdock (Arctium lappa L) investigated. This may be attributed to the variation in the different rates of fertilizer application used in the study (Ichami et al, 2019;Hammed et al, 2019). These results are in line with Qasim (2018), who reported significant differences in growth and yield parameters of burdock as influenced by different levels of nitrogen fertilization and harvesting time, but with the highest effect at 100kg/ha of nitrogen fertilizer application in burdock plant, while in this study, the application of 635kg/ha had the greatest influence.…”
Section: Discussionsupporting
confidence: 87%
“…The results of this experiment showed that fertilizer treatment combinations had significant differences in all the morphological parameters of burdock (Arctium lappa L) investigated. This may be attributed to the variation in the different rates of fertilizer application used in the study (Ichami et al, 2019;Hammed et al, 2019). These results are in line with Qasim (2018), who reported significant differences in growth and yield parameters of burdock as influenced by different levels of nitrogen fertilization and harvesting time, but with the highest effect at 100kg/ha of nitrogen fertilizer application in burdock plant, while in this study, the application of 635kg/ha had the greatest influence.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, it is important to inhibit the proliferation of bacterial or fungal pathogens around the culture medium or root area via complete sterilization when reusing culture fluids. (3,4) Sterilization includes chemical, heat, and ultraviolet sterilization. Ultraviolet sterilization is aimed at purifying water using semiconductor light sources.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical fertilizers in combination with organic manures can be effectively used to level off the yield stagnation [6]. Because organic amendments have the potential to ameliorate the threat of climate change and seasonal variation to food security [7]. The efficient use of chemical fertilizers requires an optimum level of organic matter in the soil that can be achieved by integrated use of chemical and organic fertilizers including composts [8][9][10].…”
Section: Introductionmentioning
confidence: 99%